El estudio de la literatura hispanofilipina durante el siglo XX. - Mojarro Romero, Jorge (El Colegio de México, 2018)
This paper offers a survey of the most relevant critical approaches in the field of Spanish-Filipino Literary Studies with the aim of charting its development up to the year 1999. Given the relatively limited size of the corpus, this paper will treat studies that, although not focused directly on Spanish-Filipino Literature in Spanish, highlight how the field has been defined, which works have deserved more attention, what were the criteria used to select canonical works, what periods have been established, and what dominant methodologies have been employed to date. This will allow us to draw important conclusions about the development of scholar- ship in this area during the twentieth century.